Stress coping strategies of angkringan traders in facing the COVID-19 pandemic - Nureyzwan Sabani (Nur Science Institute, 2024)
Business actors in the economic sector experienced difficulties in generating income during the Covid-19 pandemic, including angkringan traders, also known locally as Hik (Hidangan Istimewa Kampung). This study aims to describe the causal factors of stress and the coping strategies used by angkringan traders during the pandemic. The research population comprised angkringan traders in Sukoharjo, with a sample of 43 respondents. Data were collected using a questionnaire and analyzed descriptively. The results show that the leading causes of stress were fear of contracting COVID-19 and concerns about declining income. Problem-focused coping strategies included seeking financial assistance through MSME aid programs, reminding buyers to follow health protocols, and continuing to trade while implementing strict safety measures. Emotion—focused coping strategies involved learning to save money, maintaining patience, and strengthening personal resilience. Overall, angkringan traders employed a combination of practical and emotional techniques to navigate the economic and health challenges posed by the pandemic.